Exploração de grafos na educação básica - Vieira, Wellington (2024)
The present study aims to explore the application of concepts from graph theory in school practice, focusing on the following guiding question: ``What advantages are there in using graphs in Basic Education?'' To help us search for the answer, we applied some activities involving Eulerian paths, the four-color theorem, among other concepts. We proposed the creation of activities applicable to high school students at a private school in the city of Itumbiara-GO. The aim was, in addition to collecting data for this investigation, to encourage interest in science, and especially mathematics. The research is justified by allowing the integration of theory and practice for the benefit of learning, associating it with involvement in the resolution of work proposals, using concepts that are not normally seen in basic education.